What News in the Surface Chemistry of Bulk and Supported Vanadia Based SCR‐Catalysts: Improvements in their Resistance to Poisoning and Thermal Sintering. Issue 9 (18th October 2018) - Granger, Pascal; Siaka, Hermann W.; Umbarkar, Shubhangi B.
Abstract: This paper reports a short review on the impact of poisoning effects and thermal aging on the reactivity of surface vanadate species on benchmark V2 O5 −WO3 /TiO2 Selective‐Catalytic‐Reduction catalysts. A renewed interest of this SCR technology is related to its diversification notably as after‐treatment systems to treat the exhaust from Diesel engines with higher running temperature especially when SCR catalysts are coated on Diesel Particulates Filters. Particular attention is also paid to poisoning effects in conjunction with the progressive replacement of fossil fuels by bio‐fuels containing alkaline contaminants which drastically deactivate the catalyst through neutralization of strong acid sites. Most of the investigations show that better insight into the mechanisms of poisoning and aging processes is needed especially to understand the relative sensibility of various vanadate species. This could provide original guidelines to catalyst preparation and or the developments of more stable bulk systems as exemplified. Abstract : Development of thermally stable SCR vanadia‐based catalysts for stationary and mobile applications.